Empowerment of Human Resources in Wedoroanom Village, Gresik Through Stunting Prevention and Mitigation Program - Qotrunnada M, Elisa; Pratami, Rindy Asti; Kumalasari, Syalsya Putri (Journal of Health Community Service, 2023)
Stuntingis a priority health problem that describes a lack of nutritional value in children.Stunting is one of the major problems faced by the Gresik community, one of the villages with high stunting cases in Gresik is Wedoroanom village. The reason is that cases of stunting, dwarfism or malnutrition have an impact on the development of children, of which many cases are found in Wedoroanom village.The role of various parties including academics is very much needed in the process of overcoming stunting. Therefore, through the Real Work Lecture Program (KKN) aimed at Wedoroanom Village, Gresik Regency, the team wants to contribute to the process of empowering human resources with a program to prevent and overcome stunting through counseling activities, measuring nutritional status, and providing additional food recipes. The implementation methods are Wedoroanom Village Survey, Identifying Problems and Formulating Solutions, Work Program Planning, Implementation of Counseling Programs and Providing Food Recipes, Implementation of Information Programs about Pregnant Women and also Exercise Programs for Pregnant Women, Evaluation. The results of the implementation of this work program are that the Wedoroanom community is enthusiastic about empowering the community in terms of increasing knowledge and understanding the actions that need to be taken regarding the prevention and overcoming of stunting.